2015
DOI: 10.1016/j.molonc.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of the prostate cancer small‐nucleolar transcriptome reveals SNORA55 as a driver of prostate cancer progression

Abstract: Metastasis is the primary cause of death in prostate cancer (PCa) patients. Small nucleolar RNAs (snoRNAs) have long been considered “housekeeping” genes with no relevance for cancer biology. Emerging evidence has challenged this assumption, suggesting that snoRNA expression is frequently modulated during cancer progression. Despite this, no study has systematically addressed the prognostic and functional significance of snoRNAs in PCa.We performed RNA Sequencing on paired metastatic/non‐metastatic PCa xenogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 57 publications
4
34
0
2
Order By: Relevance
“…Dysregulation of snoRNAs is a signature for many cancers (Gong et al, 2017;Jorjani et al, 2016;Williams and Farzaneh, 2012), and in some cases, it has even been suggested to be a requirement for oncogenesis (Crea et al, 2016;Su et al, 2014;Zheng et al, 2015;Zhou et al, 2017), underscoring a critical need for cells to control snoRNA levels. Human cells express several hundred different variants of each of the two snoRNA types, many of which are known, or predicted, to guide the modification of specific nucleotides in pre-rRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of snoRNAs is a signature for many cancers (Gong et al, 2017;Jorjani et al, 2016;Williams and Farzaneh, 2012), and in some cases, it has even been suggested to be a requirement for oncogenesis (Crea et al, 2016;Su et al, 2014;Zheng et al, 2015;Zhou et al, 2017), underscoring a critical need for cells to control snoRNA levels. Human cells express several hundred different variants of each of the two snoRNA types, many of which are known, or predicted, to guide the modification of specific nucleotides in pre-rRNA.…”
Section: Introductionmentioning
confidence: 99%
“…En tumores metastásicos, del SNORD78 está expresado a la alta y el SNORA55 circulante (en suero sanguíneo) fue un predictor de supervivencia libre de recaída de los pacientes. La disminución forzada de la expresión del SNORD78 inhibió la proliferación y migración celular, al regular vías de señalización asociadas con factores de crecimiento y la expresión de citocinas proinflamatorias 65 . Entonces, el snoRD78 y el snoRA55 parecen ser respectivamente indicadores de un peor y mejor pronóstico de los pacientes con cáncer de próstata.…”
Section: Cáncer De Próstataunclassified
“…Por su parte, el carcinoma adrenocortical mostró la expresión diferencial de 19 snoRNAs, los cuales podrían ser usados como molécula biomarcadoras 65 .…”
Section: Osteosarcoma Y Carcinoma Adrenocorticalunclassified
“…Locus deletions of these snoRNAs enhance tumorigenesis, so they are observed in many human cancers (Siprashvili et al 2016). SNORA55 overexpression is associated with activation of oncogenic pathways in prostate tissue which is a driving force in the development of prostate cancer (PtC), while SNORA55 silencing stops proliferation and metastatic potential of PtC cells (Crea et al 2016). On the other hand, the lowered expression of SNORD47 is associated with tumorigenesis in glioblastoma, while its upregulated expression suppresses invasion of glioma cells and extends patient’s survival (Xu et al 2017).…”
Section: A Nucleolus As a Support Of Cancer Cellsmentioning
confidence: 99%